The Water Quality of Several Oxbow Lakes in Sabah, Malaysia and its Relation to Fish Fauna Distribution - Lee, Y.H.; Nyanti, L.; Stuebing, R.B.; O., Mani (Science Alert, 2006)
A record of the water quality and fish fauna composition of the Luagan Rompong oxbow lake of the Padas River near Beaufort, the Kalandaun and Kalananap oxbow lakes of the Kinabatangan River at Sukau is presented in this study. The water quality of all three oxbow lakes exhibited wide daily variation in dissolved oxygen content (3.9-12.4 mg L-1) and also large changes in daily water, especially for the Kinabatangan oxbow lakes. All three lakes demonstrated different composition of fish fauna with the Cyprinidae famili (45-80%) dominating in the lakes. The Shannon-Weiner diversity indices for fish from all the lakes were between 2.15 and 3.13 with the Kalandaun Lake at the Kinabatangan River showed highest fish fauna diversity